The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/ogx.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Group Prenatal Care

Abstract: The intent and delivery of prenatal care have evolved since its formal inception in the early 1900s. Group prenatal care offers an alternative care delivery model to the currently dominant prenatal care model. The group model has been associated with a number of improved perinatal outcomes including decreased preterm birth, higher birth weight, improved breast-feeding initiation and duration, decreased cesarean delivery, and greater patient satisfaction. This article outlines the tenets of CenteringPregnancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
13
0
5
Order By: Relevance
“…Themes and subthemes identified in the interviews were well-aligned with statistically significant increases in selfreported knowledge. Satisfaction was high: 93% of women preferred group to individual prenatal care, a result consistent with past studies (Cunningham et al, 2016;Little et al, 2013;Tandon et al, 2013;Tilden et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Themes and subthemes identified in the interviews were well-aligned with statistically significant increases in selfreported knowledge. Satisfaction was high: 93% of women preferred group to individual prenatal care, a result consistent with past studies (Cunningham et al, 2016;Little et al, 2013;Tandon et al, 2013;Tilden et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Many positive maternal and neonatal outcomes have been associated with the use of CenteringPregnancy, and studies have shown benefits when compared with individual prenatal care. Research on CenteringPregnancy has shown increased engagement by women in their own pregnancy care (Earnshaw et al, 2016;Heberlein et al, 2016;Tandon, Cluxton-Keller, Colon, Vega, & Alonso, 2013), increased visit attendance prenatally and postpartum (Tandon et al, 2013), and decreased maternal stress and anxiety during pregnancy (Heberlein et al, 2015;Heberlein et al, 2016;Ickovics et al, 2016;Tilden, Hersh, Emeis, Weinstein, & Caughey, 2014). More widely, research on CenteringPregnancy and GPC has shown increased knowledge of pregnancy, labor, and postpartum topics (Heberlein et al, 2016;Little, Motohara, Miyazaki, Arato, & Fetters, 2013;Tilden et al, 2014) and increased care satisfaction among women who participate in these programs compared with those who participate in individual prenatal care (Cunningham et al, 2016;Little et al, 2013;Tandon et al, 2013;Tilden et al, 2014).…”
Section: Available Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…We used databases (PubMed, EBSCO, Science Direct, Wiley Online, the publisher Springer) and registry pages of systematic reviews such as The Cochrane Library and Prospero. Because of our first objective, we gave priority to systematic reviews, meta-analyses and randomized clinical trials that have comparatively evaluated individual prenatal care and group models in different maternal and perinatal health outcomes 6 , 16 , 17 , 21 ( Table 2 ).…”
Section: Narrative Review Of the Literature About The Effectiveness Omentioning
confidence: 99%
“…One option that may be feasible is group prenatal care. There is a building literature to suggest that nurse/midwife led prenatal care and education, delivered via facilitated discussion to groups of 8–12 women simultaneously, is associated with large improvements in satisfaction, utilization and pregnancy outcomes [ 23 , 44 , 45 ]. In American Samoa offering group prenatal care to ‘healthy’ pregnancies (those with no complications other than overweight) may improve satisfaction and also reduce burden on the practicing physicians, potentially reducing waiting times for others.…”
Section: Discussionmentioning
confidence: 99%